ANALYSIS OF HUMAN RESOURCE DEVELOPMENT IN SUPPORTING WORKER PRODUCTIVITY OF PT. SULAWESI EARTH MINE (TBB) - Jaya, Basmala Septian; Razak, Abdul; Supriaddin, Nofal (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This study aims to find out and analyze: Human resource development in supporting Productivity at PT. Sulawesi Bumi Mine. The benefits of this study are For the development of science, the results of this research are expected to add information and knowledge about human resource development strategies in supporting worker productivity at PT. Sulawesi Bumi Mine, contribution of ideas and as input material to support the basis of similar and relevant research theories. This study uses a descriptive qualitative method. Data was collected by observation, interview .The results of the study are: (1) Human resource development at PT. Bumi Sulawesi (FFB) Mine with training that is carried out every time there is a new product or program from the company's management, (2) PT. Tambang Bumi Sulawesi (TBS) organizes additional education and refresher education to increase cooperation between workers, and (3) In increasing Work Productivity at PT. Tambang Bumi Sulawesi (FFB) each worker must analyze their work and master their respective job description.